Toward a unified Europe? Explaining cultural differences by economic development, cultural heritage and historical shocks - Sjoerd Beugelsdijk; Ton Van Schaik (European Regional Science Association (ERSA), 2003)
In this paper we study the cultural aspects of the `Europe of the regions'. We try to explain value differences in European regions. In explaining value differences between regions we build on Inglehart, who has described and empirically analysed the relationship between cultural values and economic development (1990, 1997, 2000). Inglehart has shown that economic development is linked with systematic changes in basic values. Inglehart's main argument is that economic development has a number of systematic and predictable cultural and political consequences (ibid.). However, Inglehart shows that cultural change does not follow a linear path, but in fact has two dimensions. The first relates to early industrialization and the rise of the working class. The second dimension reflects the value changes that are linked to the affluent conditions of advanced industrial society and the rise of the service sector. In addition to these findings, Inglehart finds evidence for the persistence of distinctive traditional values and conclude that cultural change may be path-dependent. The explanation of value differences is particularly interesting against the background of a unifying Europe and the idea of a `Europe of the regions'. The question we try to answer in this paper is if we can speak of cultural unification in Europe. And in case of cultural differences across European regions, the question arises if we can explain these value differences' And can we say something on the possible convergence of values across Europe? We have several important findings. First, Inglehart's thesis on economic development and cultural heritage holds true for European regions. Moreover, we find a specific regional effect of protestant heritage. Second, we show that on one of the dimensions that describe basic values – the Survival/self-expression dimension – there has been a period-specific effect in the 1990s. We argue that broad societal developments like the New Economy hype, the adoption of the single currency in Europe and – perhaps most important - the collapse of the Soviet Union and `the end of history' (Fukuyama, 1992) may have resulted in an optimistic view on the future and may have subsequently resulted in this period-specific effect when explaining value differences across European regions in the 1990s. This is an important contribution to the general thesis as developed by Inglehart, namely we have not only shown that economic development together with cultural heritage is linked with value changes, but also that unique historical shocks can have significant effects on value systems. Third, we illustrate that convergence of values – even if we allow for significant economic catch-up growth of poorer regions – takes a very long period, if it would occur anyway. The vision of the European Commission of a `Europe of the Regions' in which there would be a reasonable homogeneous regional social-economic structure across Europe and a shared European value system is therefore not built on realistic accounts of the actual cultural differences that exist in Europe.
Keywords: 330